THE IMPACT OF CHILD-FRIENDLY LIBRARIES ON EDUCATIONAL BEHAVIOR OF ELEMENTARY SCHOOL STUDENTS IN TEGAL REGENCY - Rullis, Rullis; Muljani, Sutji (Prodi PGMI FTK UIN Ar-Raniry Banda Aceh, 2026)
The low reading interest among elementary school students in Indonesia is a critical issue, often exacerbated by school library conditions that are rigid, non-ergonomic, and visually unappealing. This study aims to deeply analyze the impact of child-friendly library interior design innovations on the formation of educational behavior among students in Tegal Regency. This research serves as a response to the